Receptor subunit compositions underly distinct potencies of a muscle relaxant in fast and slow muscle fibers - Yamashita, Manami; Egashira, Yoshihiro; Nakamura, Shuntaro; Sakata, Souhei; Ono, Fumihito (Frontiers in Physiology, 2022)
A line of studies in the1960s-1980s suggested that muscle relaxants do not work uniformly on all skeletal muscles, though its mechanism has not been clarified. We showed here that a classical non-depolarizing muscle relaxant pancuronium inhibits fast muscle fibers at lower concentration compared to slow muscle fibers in zebrafish. The difference of effective concentration was observed in locomotion caused by tactile stimulation as well as in synaptic currents of the neuromuscular junction induced by motor neuron excitation. We further showed that this difference arises from the different composition of acetylcholine receptors between slow and fast muscle fibers in the neuromuscular junction of zebrafish. The difference of subunit composition and sensitivity to muscle relaxants may be conserved also in mammals.